Odpowiedź :
Odpowiedź:
[tex]a)\ \ -3-4*(-5)^2=-3-4*25=-3-100=-103\\\\b)\ \ (-2)^2-3*(-4)-7=4+12-7=16-7=9\\\\c)\ \ -6-2*(-5)^2-6^2=-6-2*25-36=-6-50-36=-56-36=-92\\\\d)\ \ -7-3*(-4)^2-10=-7-3*16-10=-7-48-10=-55-10=-65\\\\e)\ \ 6-(7-5^2)-3*(-2)=6-(7-25)+6=6-(-18)+6=6+18+6=12+18=30\\\\f)\ \ -3*(-8)-6*7^2=24-6*49=24-294=-270[/tex]
Odpowiedź:
-3-4*(-5)²=-3-4*25=-3-100=-103
(-2)²-3*(-4)-7=4+12-7=16-7=9
-6-2*(-5)²-6²=-6-2*25+36=-56+36=-20
-7-3*(-4)²-10=-7-3*16-10=-7-48-10=-65
6-(7-5²)-3*(-2)=6-(7-25)+6=6-18+6=-6
-3*(-8)-6*7²=24-6*49=24-294=-270